Analysis of GCG, CRS, and Performance Finance to the Value of Banking Stocks Listed on the Indonesia Stock Exchange - Jeane Seniman Gulo; Nizamuddin; M. Ghazali Prasetyo; Putri Pujiningtyas (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The purpose of the study was to determine and analyze the effect of GCG, CSR, and Financial Performance on Share Value. The research location is a Banking Company listed on the Indonesia Stock Exchange. The number of samples in this study was 120 financial reports. The method used is panel data regression analysis. The results showed that GCG has a positive effect on the value of shares in banking companies listed on the Indonesia Stock Exchange, CSR has a positive effect on the value of shares in banking companies listed on the Indonesia Stock Exchange and PER has no effect on the value of shares in banking companies listed on the Indonesia Stock Exchange.